Brensocatib, an oral, reversible inhibitor of dipeptidyl peptidase 1, mitigates interferon-α-accelerated lupus nephritis in mice - Chen, Kuan-Ju; Zhang, Jimin; LaSala, Daniel; Basso, Jessica; Chun, Donald; Zhou, Yuchen; McDonald, Patrick P.; Perkins, Walter R.; Cipolla, David C. (Frontiers in Immunology, 2023)
Neutrophils have been implicated in initiating and perpetuating systemic lupus erythematosus and the resultant kidney damage in lupus nephritis (LN) patients, in part through an excessive release of neutrophil serine proteases (NSPs). NSP zymogens are activated by dipeptidyl peptidase 1 (DPP1) during neutrophil maturation and released by mature neutrophils in response to inflammatory stimuli. Thus, a potential strategy to attenuate disease progression in LN would be to inhibit DPP1. We tested whether brensocatib, a highly selective and reversible DPP1 inhibitor, could mitigate LN progression in an interferon-alpha (IFNα)-accelerated NZB/W F1 mouse model. To confirm brensocatib’s pharmacodynamic effect on NSPs in this mouse strain, repeated dose studies were conducted for 7 and 14 days in naïve NZB/W F1 mice via oral gavage twice a day. Brensocatib at 2 and 20 mg/kg/day achieved a significant reduction in bone marrow NSP activities after 7 days of daily administration. To initiate LN disease progression, the mice were injected with an IFNα-expressing adenovirus. After two weeks, three brensocatib doses (or vehicle) were administered for 6 more weeks. Throughout the 8-week study, brensocatib treatment (20 mg/kg/day) significantly reduced the occurrence of severe proteinuria compared to the vehicle control. Brensocatib treatment also entailed a significant reduction in the urine albumin-to-creatinine ratio indicating decreased kidney damage, as well as a significant reduction in blood urea nitrogen level, suggesting improved renal function. Based on kidney histopathology analysis, brensocatib treatment significantly lowered both the renal tubular protein score and the nephropathy score compared to the vehicle group. A trend towards reduced glomerulonephritis score with brensocatib treatment was also observed. Lastly, brensocatib significantly reduced LN mouse kidney infiltration by various inflammatory cells. In conclusion, these results suggest that brensocatib alters disease progression in LN mice and warrant further evaluation of DPP1 inhibition in LN.